Peculiarities of Stressors Experienced by Physical Education Teachers at Work - Andrius Stočkus; Eugenija Adaškevičienė (Lithuanian Sports University, 2018)
Research background and hypothesis. The article focuses on assessment of stressors experienced by physical  education teachers in their work. As surveyed researchers notice, stress at work can cause a depressive mood, anxiety,  tiredness and, eventually, serious illnesses. Under constant and overwhelming stress, a real threat of formation of  the burnout syndrome appears. This is a condition of emotional, psychic and physical exhaustion formed under  long-lasting unsolved stresses arising in work-related situations. Stress also significantly influences work efficiency,  creativity and competitiveness. It is very important to notice that the change of personality features in a teacher  experiencing stress or, even worth, the burnout syndrome, leave traces on the other person. Thus, it is necessary to   go deeper into this scientific problem: what stressors are characteristic to the work of physical education teachers, what are the correlations with the socio-demographic variables The aim of the research was to assess work-related stressors of physical education teachers and their relation  with socio-demographic variables. Teachers of physical education (n = 118 in comprehensive schools took part in  the research. Research methods applied in the research: the data was collected using questionnaires on work-related stressors and socio-demographic information; the data obtained was processed by applying the parameter statistics, Mann- Whitney (U) criterion was employed as well. Research results. The research showed that teachers of physical education listed the following as the most important sources of stress at work: abundance of various documents and other "papers", reforms of the educational system and high responsibility for pupils. Unfavourable work conditions, psychological climate at school, work with groups of pupils of different genders, problems with pupils' parents almost did not cause stress to teachers of physical education. Younger teachers or those less experienced in pedagogical work felt more stress about high numbers of pupils in a sports hall than their senior or more experienced colleagues did. Senior and more experienced teachers of physical education emphasised that they underwent the following more intensive work-related stressors: high responsibility for others, abundance of various documents and other "papers", underestimation of physical education teachers' work. Men were unsatisfied with low salaries, and women indicated that the attitude of teachers in other subjects towards physical education caused dissatisfaction with work. Male teachers' low salaries and female teachers' perceived unappreciated attitude towards physical education caused stress to them. Teachers working in cities, towns assessed pupils' disrespect and high numbers of pupils in forms as a bigger stressor than teachers of physical education in districts. Physical education teachers working in gymnasiums assessed competition inside an educational institution as a stronger stressor rather than educators working in the main or secondary schools. Discussion and conclusions. In the aspect of work-related stressors of physical education teachers, teachers list abundance of various documents and reforms of the educational system as main sources of stress at work. Negative attitude of other colleagues towards teachers of physical education as well as competition among staff at school, and, on the other hand, negative attitude of pupils towards physical education have been revealed. Analysis of correlations  between  work-related  stressors  and  socio-demographic  variables  suggests  that  younger  pedagogues  experience  higher stress caused by reforms of the educational system and a high amount of pupils in a sport hall during lessons  in comparison to their senior colleagues; while senior teachers of physical education emphasise responsibility as a higher work-related stress. Keywords: physical education, teachers' stress, burn out.